How do we build power in coalition? Rethinking union-community coalition types 12 years on. (2nd January 2018) - Tattersall, Amanda
ABSTRACT: Union-community coalitions are an increasingly frequent phenomenon in the industrial landscape. In 2005, 'There is Power in a Coalition' sought to build a typology to understand various kinds of coalitions and define their different features. This article reviews that typology then applies it to the Sydney Alliance. The Sydney Alliance is a broad-based coalition of religious organisations, unions and community organisations that uses community organising to make Sydney a better place for everybody. It has included up to eleven unions at its peak and is an example of a Deep Coalition. The article combines the typology and the practices of the Sydney Alliance to build a more complex and detailed understanding of how Deep Coalitions work and what is likely to make them successful.